Father Involvement in Early Childhood Care during the Covid-19 Pandemic - Ni Putu Eka Maryuni; Luh Ayu Tirtayani; Didith Pramunditya Ambara (Journal of Psychology and Instruction, 2022)
In the process of distance learning during the Covid-19 pandemic, early age students have to study from home and need parental guidance. However many parents are still less able to guide their children in online learning activities. This study aimed to analyze fathers’ involvement in early childhood care during the Covid-19 pandemic. This type of study was qualitative. The approach used in this study was a case study. Data collection used interviews and focus group discussions (FGD) methods. The instrument used was a questionnaire. The technique used to analyze the data was a descriptive qualitative analysis of data analysis by Miles and Huberman. The results of this study were as follows. First, fathers still carry out learning activities but do not leave their duties as a father. Second, fathers still take the time to present themselves to their children by accompanying them to activities. Third, the responsibility given by the father to the child is indeed more dominant in financial terms. Fourth, fathers’ activities when they are with their children are various ways. It was concluded that fathers still made time for their children during the Covid-19 pandemic.